Strategy For Developing MSME Through Sharia Microfinance Institutions - Riza, Akmal; Arifin, Muhammad; Nazar, Nazar (Program Studi Perbankan Syariah FEBI UIN Ar-Raniry, 2025)
Providing access to financing to Micro, Small and Medium Enterprises (MSMEs) carried out by banking financial institutions and microfinance institutions can have a positive impact on the development of MSMEs. The development of MSMEs can be carried out by offering financing products based on sharia principles. This research aims to determine the strategies and obstacles of LKMS Mahirah Muamalah in helping the development of MSMEs in the City of Banda Aceh. This research uses a qualitative descriptive method with field research data collection through interviews, observation and documentation. The research results show that LKMS Mahirah Muamalah carries out 3 types of strategies, namely: information provision strategy, provision of financing products, and service strategy. Then the obstacles faced by LKMS Mahirah Muamalah are divided into 2, namely intern (There is still a lack of human resources/employees, distribution of financing is still limited), as for extern obstacles: There is still minimal public literacy regarding LKMS, weak understanding and management skills of MSMEs